Adenosine signaling in Drosophila - Kučerová, Lucie (Jihočeská univerzita, 2013)
This thesis characterizes adenosine signalization in Drosophila and describes response to adenosine in various cell types. Extracellular adenosine mediates most of its physiological effects through its receptors but recent data also indicate that adenosine transport also has important physiological functions. It was shown in this thesis that adenosine stimulates only cAMP second messenger system in Drosophila cells endogenously expressing AdoR. The pharmacological profile of the DmAdoR was established using the cAMP functional assay. The utility of the agonist 2-chloroadenosine and antagonist SCH58261 were examined in flies in vivo and compared with phenotypes of DmAdoR mutants. The responses of Drosophila cells to adenosine mediated by adenosine transport were also examined. Different cell types exhibited striking differences in adenosine uptake and adenosine recycling that were closely connected with the regulation of carbohydrate and lipid metabolism. This thesis provides an important foundation for the study of interactions between adenosine receptor and adenosine transport.
Adenosine signaling in Drosophila
Keywords: AdoR; calcium; CG5793; cyclic AMP; GloSensor; GPCR; adenosine recycling; nucleoside transport; ATP synthesis; AdoR; calcium; CG5793; cyclic AMP; GloSensor; GPCR; adenosine recycling; nucleoside transport; ATP synthesis